CONSERVATIVE TREATMENT OF BENIGN PROSTATIC HYPERPLASIA: CLINICAL OUTCOMES AND IMPLICATIONS FOR PATIENT MANAGEMENT (International journal of medical sciences, 2026)
Benign prostatic hyperplasia is a prevalent urological condition affecting middle-aged and elderly men, characterized by progressive enlargement of the prostate gland and the development of lower urinary tract symptoms. These symptoms significantly impair patients’ quality of life and often necessitate medical intervention. Conservative treatment methods, including pharmacological therapy, serve as a first-line approach, particularly in patients with mild to moderate disease. This study evaluates the clinical outcomes of conservative management, focusing on symptom reduction, improvement of urinary function, and enhancement of quality of life. Results indicate that non-surgical therapy effectively alleviates lower urinary tract symptoms, stabilizes disease progression, and minimizes the need for surgical intervention. Early initiation and consistent adherence to conservative treatment are essential for achieving optimal outcomes and maintaining patient safety. Overall, conservative management provides a safe, effective, and patient-centered approach in the comprehensive care of benign prostatic hyperplasia.